1999
DOI: 10.1590/s0100-204x1999001100022
|View full text |Cite
|
Sign up to set email alerts
|

Produção Animal Em Pastagem De Milheto Sob Diferentes Níveis De Nitrogênio

Abstract: Termos para indexação: adubação nitrogenada, carga animal, desempenho por animal, novilhos, produtividade animal, uréia. ANIMAL PRODUCTION IN PEARL MILLET PASTURE UNDER DIFFERENT NITROGEN LEVELSABSTRACT -An experiment was conducted at the Universidade Federal de Santa Maria, in Santa Maria, RS, Brazil, with the objective of evaluating the effects of three N levels (0, 150 and 300 kg/ha), in pearl millet (Pennisetum americanum (L.) Leeke) cv. Comum, on animal production. Beef steers were assayed through daily l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
15

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 3 publications
(5 reference statements)
1
5
0
15
Order By: Relevance
“…The high basal tillering, higher leaf:stem ratio and high density of green leaves in Pearl millet under continuous grazing are obtained when the canopy is managed with an average height of 30cm, and it can be considered as a recommendation of management for this species (Moojen et al, 1999). This value is close to that observed in the database studies (Tab.…”
Section: Resultssupporting
confidence: 83%
“…The high basal tillering, higher leaf:stem ratio and high density of green leaves in Pearl millet under continuous grazing are obtained when the canopy is managed with an average height of 30cm, and it can be considered as a recommendation of management for this species (Moojen et al, 1999). This value is close to that observed in the database studies (Tab.…”
Section: Resultssupporting
confidence: 83%
“…Entre as espécies forrageiras utilizadas no RS, na estação estival, destacase o milheto por possuir características de alta produção de forragem, com alta qualidade, por suportar cargas animais elevadas e por sua adaptação à diversidade de condições ambientais do Estado (MOOJEN et al, 1999;SANTOS et al, 2005). Em pastagem de milheto manejada com diferentes alturas, CASTRO (2002) observou em cordeiros ganho individual médio de 121,7g dia -1 na pastagem com e 33,3cm de altura e ganho por área de 609,3kg de PV ha -1 na altura média de 29,2cm.…”
Section: Introductionunclassified
“…These values are slightly lower than this experiment, however, other researches, shows similar stocking rate values. Moojen et al (1999), working with a forage mass of 3,168 kg of DM/ha observed on pearl millet a stocking rate of 1,585, 2,225 e 2,877 kg of LW/ha respectively to the N levels of and 0, 150 and 300 kg of N/ha.…”
Section: Resultsmentioning
confidence: 99%